Professional Development of Preschool Teachers for Inclusive Educational Practice - Iva N. Manić (Društvene i Humanističke Studije, 2023)
With the development of globalization and continuous changes in terms of the formal inclusion of children in social systems, the need for acceptance and inclusion in the system of children with special social support needs has been recognized. The research aimed to determine the circumstances that are significant for the professional development of preschool teachers (frequency, motivation, forms, self-assessment of abilities, application of new knowledge, and cooperation) for the needs of inclusive educational practice in preschool institutions. A convenience sample of 141 preschool teachers from the territory of the cities of Pirot and Niš participated in the research. Teachers expressed their views on this topic using a Likert-type scale composed of 52 items divided into 7 subscales, through the use of a Google Forms questionnaire. The obtained results show that: teachers consider continuous professional development for the organization and implementation of inclusive practice to be significant and necessary; teachers enhance their expertise in the field of inclusion through activities such as thematic workshops, online programs, and joint activities with other teachers, while individual and group research is less frequently applied. Preschool teachers with fewer years of work experience apply various forms of professional development in the field of inclusion. Teachers who implement inclusive educational practices with the nursery or younger preschool group are less motivated for professional development in the field of inclusion. Preschool teachers with less work experience tend to apply new knowledge in the field of inclusion (acquired through professional development). Based on the obtained results, it is recommended to encourage and support teachers in choosing activities for professional development that contribute to the development of skills and knowledge for working in inclusive educational practice.